Persepsi Mahasiswa Unimed Terhadap Penggunaan Akal Imitasi Dalam Mata Kuliah Exploitation De Ressources Numériques En Classe Du Fle - William Anderson Hutapea; Jhoni Maslan; Marice Marice (Journal Of Dehasen Educational Review, 2026)
This study aims to examine students’ perceptions of the use of artificial intelligence in the course Exploitation de Ressources Numériques en Classe du FLE at the French Language Education Program, Universitas Negeri Medan (UNIMED). The course emphasizes the integration of digital resources in the teaching of French. Using a descriptive quantitative approach, data were collected from second-semester students through questionnaires. The findings show that most students perceive artificial intelligence as a beneficial tool, particularly for generating teaching ideas, translating texts, and designing instructional materials. Students reported significant support in terms of creativity and efficiency. However, they also acknowledged the potential risks of dependency and stressed the importance of critical thinking when using AI-generated outputs. In this regard, the lecturer's role was seen as crucial, as ethical guidance had already been provided during the course, allowing students to use AI responsibly. Some technical barriers, such as limited internet access and inadequate devices, were still present. Overall, students expressed enthusiasm and openness, while remaining reflective in utilizing AI as part of digital-based French language learning. This study highlights the need to strengthen pedagogical strategies and sustain ethical guidance in integrating artificial intelligence within higher education settings.